FITUR BAHASA PEREMPUAN YANG DIGUNAKAN PEREMPUAN DI BERBAGAI PERAN PUBLIK - Kurnia, Aliya Syifa; Nurulaen, Yuyun; Ruminda, Ruminda (eScience Humanity Journal, 2025)
Since the rise of the second wave of feminist movement, the contribution of women in professional fields has significantly increased. As women occupy these public roles, studies found that they can still adopt the distinct language, which Lakoff (1975) termed as women's language features. This research aimed to compare and analyze the use of these features among four popular professional public roles in the United States, namely, politician, businesswoman, lawyer, and artist. Furthermore, four figures are selected with consideration of one representative per each role. The figures were Kamala Harris, Indra Nooyi, Ruth Bader Ginsburg, and Selena Gomez, respectively. A qualitative method was employed, using interview transcripts and audio from YouTube videos. The analysis included all ten recognized features, such as lexical hedges, tag questions, intensifiers, empty adjectives, and others. These features were identified through close reading of the transcripts and careful listening to the audio, then categorized based on the original framework. The findings showed that there were variations in the frequency of feature occurrences across the roles. Moreover, the tendencies appeared to functioned the women's language features as a deliberate way to meet job requirements.